2016
DOI: 10.1016/j.eurpsy.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Modality Shift Effect in Psychiatric Disorders – a New Look at an Old Paradigm

Abstract: Our data support newer theories about underlying pathophysiological mechanisms and observable behavioural phenomena occurring across the different diagnostic categories, thereby supporting a dimensional approach in the diagnosis and clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Attentional control may be affected in a number of populations and the MSE paradigm has been used to investigate attention across the senses, most commonly in studies of schizophrenia (see Mannuzza, 1980, for a review). This work has indicated that MSEs between visual and auditory targets are increased in the condition (Ferstl et al, 1994;Krag et al, 2017;Spring, 1980). The MSE has also been investigated in dyslexia (Harrar et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Attentional control may be affected in a number of populations and the MSE paradigm has been used to investigate attention across the senses, most commonly in studies of schizophrenia (see Mannuzza, 1980, for a review). This work has indicated that MSEs between visual and auditory targets are increased in the condition (Ferstl et al, 1994;Krag et al, 2017;Spring, 1980). The MSE has also been investigated in dyslexia (Harrar et al, 2014).…”
Section: Introductionmentioning
confidence: 98%